2010
DOI: 10.1016/j.msea.2009.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber angle orientation and stacking sequence on mixed mode fracture toughness of carbon fiber reinforced plastics: Numerical and experimental investigations

Abstract: This paper focuses on the effect of fiber orientation and stacking sequence on the progressive mixed mode delamination failure in composite laminates using fracture experiments and finite element (FE) simulations. Every laminate is modelled numerically combining damageable layers with defined fiber orientations and cohesive zone interface elements, subjected to mixed mode bending. The numerical simulations are then calibrated and validated through experiments, conducted following standardized mixed mode delami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 28 publications
(56 reference statements)
3
39
0
Order By: Relevance
“…Nevertheless, the shear cusps in the MMF specimen were less significant and more random compared to the ENF specimen, which was similar to the observation by Naghipour et al [6]. In addition, the roughness of the MMF specimen was less than the ENF specimen [7]. On the other hand, matrix cracking seemed to be another major failure mechanism.…”
Section: Failure Analysis and Prevention 42supporting
confidence: 85%
See 3 more Smart Citations
“…Nevertheless, the shear cusps in the MMF specimen were less significant and more random compared to the ENF specimen, which was similar to the observation by Naghipour et al [6]. In addition, the roughness of the MMF specimen was less than the ENF specimen [7]. On the other hand, matrix cracking seemed to be another major failure mechanism.…”
Section: Failure Analysis and Prevention 42supporting
confidence: 85%
“…However, significant shear cusps were observed on the 0 l a y e ri nt h e4 5 direction, which was attributed to the shear mode loading. It has also been reported that the high shear mode would draw large shear cusps [6,7]. A certain amount of matrix cracking was observed on the 45 layer, which was believed to be due to the interaction between 0 and 45 layers during shearing.…”
Section: Failure Analysis and Prevention 42mentioning
confidence: 89%
See 2 more Smart Citations
“…0.32 3.45 6 10.3 127.6 Table 3 The strength properties of the unidirectional laminate made of AS4/APC2 (PEEK) (Naghipour et al, 2010) where 1 and x denote the fiber direction while 2 and y represent for the matrix direction. Moreover, the subscript T is representing for the tension and C for the compression properties of the laminate.…”
Section: Tablementioning
confidence: 99%